Attachment and belonging, nineteenth century Whananaki : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, New Zealand - Tautari, Rowan (Massey University, 2009)
Attachment and belonging to place can be expressed in a myriad of ways. At its core is the need to legitimise presence. Historically, several strategies have been employed by different individuals or groups to establish their claim to Whananaki. This thesis explores attachment and belonging from several perspectives – from that of hapu who competed amongst each other for resources, a settler who affected to legalize a pre-Treaty of Waitangi transaction, government officials securing Crown ownership culminating in a sale in 1864, Maori drawn to the developing village settlement who married into local families, and finally the village settlers who attempted to transform the land into a familiar countryside. The paradox of belonging but not quite belonging was played out in many contexts at Whananaki, including through landmarks and their associated narratives. Landmarks can be sites asserting ancient beginnings, carefully crafted props validating legal title, symbols of progress and development, memorials denoting loss and abandonment, or neutral ground. In looking at the narratives that affix landmarks to place, we can arrive at a closer understanding of how residents of nineteenth-century Whananaki viewed and defined their environment.
Keywords: Maori; Land tenure; Land settlement; Whananaki; New Zealand; 19th century; Nineteenth century; History